Needs Assessment for Developing Animation Video in Communication Learning - Pradana, Hirnanda Dimas (Universitas Sebelas Maret, 2023)
In today's digital era, the development of the world of education has increased quite rapidly since it can facilitate learning wherever and whenever, according to student needs. Such as the presence of various alternative media to facilitate the learning process; one is an animated video, which can be used to effectively and efficiently fulfill learning needs. Several studies have revealed that animated videos play a significant role in increasing student learning outcomes. Because the animated video can make students appear as if they are faced with a real situation, it can strengthen their understanding of the material conveyed. This quantitative descriptive research used a survey method carried out in August-September 2022. From the research, it can be concluded that animated videos are highly needed in the Introduction to Communication Course. Students need learning media to accommodate their learning needs and be used anywhere and anytime. Animated videos are also required because students feel the learning media can increase their motivation.